2022
DOI: 10.1111/nph.17990
|View full text |Cite
|
Sign up to set email alerts
|

OsMADS14 and NF‐YB1 cooperate in the direct activation of OsAGPL2 and Waxy during starch synthesis in rice endosperm

Abstract: Summary Starch synthesis makes a dramatic contribution to the yield and nutritional value of cereal crops. Although several starch synthesis enzymes and related regulators have been reported, the underlying regulatory mechanisms of starch synthesis remain largely unknown. OsMADS14 is a FRUITFULL (FUL)‐like MADS‐box gene in rice (Oryza sativa). Here we show that two null mutations of OsMADS14 result in a shrunken and chalky grain phenotype. It is caused by obviously defective compound starch granules and a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The activities of SUS, UGPase, and phosphorylase 1 (Pho1) are key indicators reflecting the differences in sink strength and grain filling capacity between indica and japonica rice (Wakabayashi et al, 2021). Moreover, starch biosynthesis genes, such as OsAGPL3, GBSSI, OsSSIIa, SBEI, ISOAMYLASE 2 ( ISA2 ), and OsBEIIb , are under the control of different TFs that affect grain filling (Wang et al, 2013; Schmidt et al, 2014; Wang et al, 2020a; Feng et al, 2022). Although the above‐mentioned metabolic factors are key indicators of grain filling, few studies have conducted a combined analysis of all enzymes and intermediate metabolites and their effect on grain filling.…”
Section: Four Biological Pathways That Directly Affect Grain Fillingmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of SUS, UGPase, and phosphorylase 1 (Pho1) are key indicators reflecting the differences in sink strength and grain filling capacity between indica and japonica rice (Wakabayashi et al, 2021). Moreover, starch biosynthesis genes, such as OsAGPL3, GBSSI, OsSSIIa, SBEI, ISOAMYLASE 2 ( ISA2 ), and OsBEIIb , are under the control of different TFs that affect grain filling (Wang et al, 2013; Schmidt et al, 2014; Wang et al, 2020a; Feng et al, 2022). Although the above‐mentioned metabolic factors are key indicators of grain filling, few studies have conducted a combined analysis of all enzymes and intermediate metabolites and their effect on grain filling.…”
Section: Four Biological Pathways That Directly Affect Grain Fillingmentioning
confidence: 99%
“…A recent study determined that OsMADS14 regulates grain filling by interacting with NF‐YB1 to promote the transcription of OsAGPL2 and Wx . Mutations of OsMADS14 result in a shrunken and chalky grain phenotype (Feng et al, 2022).…”
Section: Genes and Molecular Mechanisms Underlying Grain Filling In C...mentioning
confidence: 99%
“…Several transcription factors have been reported to promote or suppress the expression of SSRGs that directly influence RS formation, such as basic leucine zipper (bZIP), nuclear factor-Y (NF-Y), myelocytomatosis (MYC), and MADS-box proteins ( Zhu et al., 2003 ; Bello et al., 2019 ; Wang et al., 2020a ; Niu et al., 2020 , 2021 ; Feng et al., 2022 ), suggesting possible roles for these transcription factors in RS formation. In rice, the bZIP family member OsbZIP33 can associate with the ACGT motif in the promoter regions of Wx and SBEI genes and promote their expression ( Yang et al., 2001 ; Cai et al., 2002 ).…”
Section: Genetic Regulation Of Rs Contentmentioning
confidence: 99%
“…Recent research showed that the MADS-box family member OsMADS14 interacts with NF-YB1 and directly binds to the CArG-box in the promoters of OsAGPL2 and Wx to promote their transcription. Mutations in OsMADS14 changed the shape and size of starch granules, resulting in a significant reduction in total starch and AC and an increase in soluble sugar content ( Feng et al., 2022 ). Taken together, these transcription factors may form a complex regulatory network to regulate expression of the Wx gene, thereby affecting the synthesis of amylose and the fine structure of starch, potentially influencing RS content.…”
Section: Genetic Regulation Of Rs Contentmentioning
confidence: 99%
“…FLOURY ENDOSPERM 2 ( FLO2 ), a member of a conserved gene family in plants, encodes a tetratricopeptide repeat domain (TPR)-containing protein located in the nucleus ( She et al., 2010 ; Wu et al., 2015 ; Kolli et al., 2019 ; Suzuki et al., 2020 ). It has been reported that FLOURY ENDOSPERM 2 could not only modulate the expression of starch synthesis-related genes including OsAGPL2, OsAGPS2b, OsGBSSI, OsBEI, OsBEIIb, OsISA1 and OsPUL , but also directly impact on the amylose biosynthesis by manipulating the splicing efficiency of Wx pre-mRNA ( Wu et al., 2015 ; Cai et al., 2022 ; Feng et al., 2022 ; Sreenivasulu et al., 2022 ). Previous studies have shown that flo2 , the loss-of-function mutant of FLOURY ENDOSPERM 2 , produced two distinct phenotypes, one with white and floury endosperm, and the other with dull grain ( She et al., 2010 ; Hunt et al., 2013 ; Boehlein et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%